PENERAPAN MESIN TEKNOLOGI PASTEURISASI SUSU KAMBING PADA UMKM TANAH JAWA DI SIMALUNGUN - Sigalingging, Candra; Sigalingging, Riswanti; Harahap, Siti Nurlani (Nusantara Hasana Journal, 2025)
The limited understanding of MSME partners regarding pasteurization technology, particularly better pasteurization equipment, results in poor pasteurization outcomes and frequent spoilage of milk during goat milk production, such as during the milking process, pasteurization, and spoilage of goat milk due to harmful bacteria. Goat milk often spoils due to bacterial contamination and a lack of hygiene during the goat milk production process, making the milk easily damaged and its shelf life very short. and the lack of education regarding dairy product diversification, bookkeeping management, and halal certification are obstacles to the development of MSMEs. The purpose of this service is to provide milk pasteurization machinery, conduct training, and introduce modern milk pasteurization machine technology that can increase the production of goat milk by the Geshine House Partners. This service was carried out as one solution to the problems faced by partners thru training on the use of pasteurization technology, bookkeeping management, PIRT (Home Industry Permit), halal certification, and the provision of milk pasteurization equipment. The activities were conducted thru training on the use of pasteurization technology, business bookkeeping management, and halal certification training. The use of a milk pasteurization machine has improved the quality of goat milk production from Mitra's business, and has made the packaging process easier to maintain shelf life, thus optimizing the productivity of Geshine's house goat milk production.